Leisure education, community development, and populations with special needs - Sivan, Atara 1957-; Ruskin, Hillel (Cabi Pub., 2000)
This book is a result of an output of a Commission of the World Leisure and Recreation Association (WRLA) to examine the role of leisure and education for leisure activities among people with special needs living in the community, requiring social or health services outside hospital. It provides a conceptual and practical framework for understanding the role of leisure education for community development with a special emphasis on special populations. It will also serve the reader as a foundation for developing models and programmes for leisure education within community settings.--Publisher's website.